An Empirical Examination of Marketing Mix Elements and Customer Perceived Value in Retail Industry (Journal of Entrepreneurship and Business, 2021)
This paper is designed to examine the effects of marketing mix elements on customer perceived value in the retail industry in Malaysia. The data were collected from 278 visitors of department stores in East Coast Malaysia using the survey method. The data were analyzed with SPSS and structural equation modelling after receiving the responses from the participants. The findings show that marketing mix elements have significant positive effects on perceived value. Specifically, it is found that advertising and distribution intensity have positive and significant effects on perceived value. Additionally, the outcomes indicate that price and store location have significant positive effects on customer perceived value. Finally, the results confirm that store image plays a significant role in affecting customer perceived value. These findings improve our understanding of the importance of the selected marketing mix elements in affecting customer perceived value in retail industry settings.
Keywords: Array; Array; Array